Kajian Penambahan Filtrat Kunyit dan Tartrazin Pada Edible Film Berbasis Pati Talas Serta Aplikasinya Untuk Mempertahankan Mutu Dodol Substitusi Rumput Laut (Eucheuma cottonii) - Noor Harini; Mochammad Wachid; Tyas Anugrah Hirgawati (Food Technology and Halal Science Journal, 2020)
This research studied the effect of natural colorant (turmeric filtrate) additions compared to synthetic colorant (Tartrazine) additions in taro starch-based edible film on the quality of dodol that substituted with seaweed. This research used a Randomized Block Design with Orthogonal Contrast. The treatment factor consist of turmeric filtrate additions in 1%, 2%, 3%, Tartrazin additions in 0,003%, 0,005%, 0,007% and without colorant as control treatment. Parameters that analyzed consist of thickness, color, transparency, tensile strength, elongation, water vapor transmission rate of edible film, moisture content, fat content, total plate count, texture and organoleptic value of dodol at the 0, 3rd, 6th day of storage. The research result shows that the additions of turmeric filtrate had an effect on increasing thickness, tensile strength, transparency, brightness (L), yellowness (b+), and decreasing the elongation and WVTR of edible film. Meanwhile, the additions of Tartrazin had an effect on increasing transparency, brightness (L), and yellowness (b+). The results of moisture content, fat content, TPC, and texture of dodol showed that the addition of turmeric filtrate is better to maintain the quality of dodol during storage. Additions of 3% turmeric filtrate as the best treatment, has 30.24% and 31.40% in moisture content, 1.16% and 0.97% in fat content, 4.0x103 CFU/g and 0.9x104 CFU/g in TPC, 15.30 N/mm and 14.03 N/mm in texture, 3.53 and 3.63 in color organoleptic value, 3.65 and 3.60 in aroma value and 3.75 and 3.73 in taste value during the 3rd and 6th day of storage.